2017
DOI: 10.1038/s41598-017-13478-x
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of the Na+-Ca2+ exchanger (NCX) in glutamate-enhanced cell survival in cardiac cells exposed to hypoxia/reoxygenation

Abstract: Myocardial ischemia culminates in ATP production impairment, ionic derangement and cell death. The provision of metabolic substrates during reperfusion significantly increases heart tolerance to ischemia by improving mitochondrial performance. Under normoxia, glutamate contributes to myocardial energy balance as substrate for anaplerotic reactions, and we demonstrated that the Na+/Ca2+ exchanger1 (NCX1) provides functional support for both glutamate uptake and use for ATP synthesis. Here we investigated the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 56 publications
4
32
0
Order By: Relevance
“…Under both physiological and pathological conditions glutamate can contribute to cellular energy balance as substrate for anaplerotic reactions, and we demonstrated that NCX1 provides functional support for both glutamate uptake and ATP synthesis 10 , 11 , 19 . Therefore, we investigated whether the protective effect of glutamate could be ascribed to its potential to sustain ATP synthesis.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…Under both physiological and pathological conditions glutamate can contribute to cellular energy balance as substrate for anaplerotic reactions, and we demonstrated that NCX1 provides functional support for both glutamate uptake and ATP synthesis 10 , 11 , 19 . Therefore, we investigated whether the protective effect of glutamate could be ascribed to its potential to sustain ATP synthesis.…”
Section: Resultsmentioning
confidence: 73%
“…It is well established that EAATs mediate the high-affinity uptake of glutamate. We demonstrated that under both physiological and pathological conditions 10 , 11 , 19 , glutamate entry into the cells through EAAT3 is functionally related to NCX1 activity 10 , 11 . Therefore, once established that NCX1 was essential to mitigate cell injury, we explored whether EAAT3 activity could also be mandatorily required.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations